(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Two unknown impurities were detected during the related substance analysis of the Silodosin crude sample using High-Performance Liquid Chromatography. These impurities were isolated using preparative HPLC and then subjected to LCMS for mass determination. Structural elucidation has been carried out using NMR (1H NMR, 13C NMR) spectroscopy. These impurities were discovered to have a structural alert, which was confirmed by the Insilico prediction model indicating that they were Potentially Genotoxic Impurities (PGI’s). A genotoxic assessment of these impurities was done using the Insilico prediction model for genotoxicity (VEGA and Toxtree). These impurities have not been reported elsewhere, to the best of our knowledge. Thus, a HPLC-UV method was developed and validated for the determination of these impurities at the TTC level. The proposed method was validated in terms of Specificity, Precision, Accuracy, Linearity and Robustness as per ICH guidelines. The LOD and LOQ of the method were established to be 0.0018 ppm and 0.055 ppm with respect to test concentration (1000 µg mL-1 silodosin).